Pengembangan Monitoring Jaringan Menggunakan The Dude Pada CV. Ketahun Jaya - Bagus Putra Wijaksana; Khairil, Khairil; Hari Aspriyono (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
In this increasingly developing era, computer technology is improving so quickly. In today's increasing technology, computer networks are widely used in all fields, one of which is government, making it easy for users to exchange information quickly and easily. The aim of this research is how to find out availability status, response time and internet usage traffic with The Dude as network monitoring at CV. Ketahun Jaya. The research method applied in this research is the Network Development Life Cycle (NDLC), where the author will use six stages in accordance with the cycle of the Network Development Life Cycle (NDLC) itself, namely: Analysis, Design, Simulation Prototyping, Implementation, Monitoring and Management . Based on the results of several tests carried out, the author concludes that this research is in accordance with the problem formulation raised, where the development of network monitoring using a microtic-based dude using the Network Development Life Cycle (NDLC) method is very helpful for the problems that have occurred all this time. After successfully implementing it using Telegram messenger on The Dude application which utilizes the Telegram Bot API, a conclusion can be drawn, namely the system that has been built on CV. Ketahun Jaya is able to send messages in real time to network administrators for both monitoring from the local network and remote access from outside the local network.